HOW THE BRAIN LEARNS NEW WORDS: VOCABULARY ACQUISITION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the process of vocabulary acquisition, its connection to the brain, common challenges that learners encounter, effective strategies for memorization and retention, and practical implications for both students and teachers.